2021
DOI: 10.2147/pgpm.s317229
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Observation of Gene Polymorphism of Olanzapine or Aprepitant in Prevention of CINV

Abstract: The present study aims to investigate the correlation between the gene polymorphisms of the multidrug resistance protein 1 (ABCB1), the intron region of transcriptional factor (GTF2E1) and catechol-O-methyltransferase (COMT), dopamine receptor (DRD2), and the control of chemotherapy-induced nausea and vomiting (CINV) by olanzapine or aprepitant in a Chinese population under a fractionated cisplatin dosing pattern. Methods: Antiemetic treatment with 5 mg of olanzapine or aprepitant triplet therapy was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Decoding the reasons for these variations in efficacy is difficult due to multiple genetic and non-genetic factors. 5 Nonetheless, publication bias and other biases must be ruled out for these variations. In this background, it is difficult to accurately quantify the benefits of Our out-of objective meta-analysis result of three trials comparing olanzapine vs. NKRAbased triple-drug regimen head-to-head, show no significant difference between the comparison groups.This was evident in the outcome measuresof CR and 'no nausea' in all three phases of CINV.…”
Section: Characters Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Decoding the reasons for these variations in efficacy is difficult due to multiple genetic and non-genetic factors. 5 Nonetheless, publication bias and other biases must be ruled out for these variations. In this background, it is difficult to accurately quantify the benefits of Our out-of objective meta-analysis result of three trials comparing olanzapine vs. NKRAbased triple-drug regimen head-to-head, show no significant difference between the comparison groups.This was evident in the outcome measuresof CR and 'no nausea' in all three phases of CINV.…”
Section: Characters Of Included Studiesmentioning
confidence: 99%
“…1-4 However, the above triple-drug regimen's efficacy in preventing nausea, especially delayed phase nausea, is incomplete and subjected to individual variations. 4,5 NKRA-based regimens were found to be most effective in preventing CINV, but their efficacy in preventing delayed nausea is comparatively low. 4 To overcome this disadvantage and as a cheaper alternative to NKRAs, olanzapine was tested and found to be equally efficacious in relieving vomiting and superior in relieving delayed phase nausea.…”
Section: Introductionmentioning
confidence: 99%
“…CINV can lead to electrolyte imbalance, dehydration, malnutrition, and esophageal damage, which not only affects the quality of life of patients, but also reduces overall survival and increases treatment costs [ 1 ]. A review of clinical trials identified several clinical risk factors for CINV: female sex, younger age, history of low-dose alcohol consumption and dizziness [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study is based on our previous study of ABCB1 rs1045642, female is an independent risk factor for CINV [ 1 ]. We combined the 42 SNPs of metabolic enzymes, transporters and targeting receptors reported in domestic and foreign literatures that may be related to CINV to explore the relationship between related SNPs and CINV susceptibility.…”
Section: Introductionmentioning
confidence: 99%